The role of law in the construction of gender identities: rethinking gender analysis from the contributions of critical theory - Garbay Mancheno, Susy (2018)
This paper gathers some of the debates proposed by critical theories, which emphasize on the analysis of law beyond its formal aspect, providing evidence that the law acts in different dimensions, thus producing categories that, at first sight, are identified with difficulty, but are nonetheless relevant in the production of meanings that contribute to keeping the prevailing social order. From this perspective, the law is observed as a social discourse that produces the object over which it intervenes, gives meaning to people’s behavior and legitimizes the structures of domination. Feminist theories, which hold on to this position, propose the promlematization of the gender and law relationship, identifying in its discourse the cultural codes that are used in the construction of gender identities.